2021
DOI: 10.1097/wnf.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intranasal Dexmedetomidine During Recovery From Sevoflurane Anesthesia in Children: A Systematic Review and Meta-analysis

Abstract: Background Intranasal drip of dexmedetomidine in children with sevoflurane anesthesia can reduce anesthesia and restlessness. However, there is still some controversy. We conducted a meta-analysis to explore the effect of intranasal infusion of dexmedetomidine on the quality of recovery during the recovery period, to provide certain guidance for clinical application. Methods Web of Science, PubMed, Embase, and the Cochrane Library were used for literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
2
2
2
Order By: Relevance
“…Postoperative nausea and vomiting are common complications after surgical procedures. Our results showed that the incidence of nausea and vomiting in the experimental group was significantly lower than that in the control group (P<0.05), which was consistent with the findings of Xu et al ( 39 ). This suggests that the synergistic effect of dexmedetomidine and anesthetics can significantly reduce the dosage of propofol and opioids, thereby reducing the incidence of nausea and vomiting.…”
Section: Discussionsupporting
confidence: 93%
“…Postoperative nausea and vomiting are common complications after surgical procedures. Our results showed that the incidence of nausea and vomiting in the experimental group was significantly lower than that in the control group (P<0.05), which was consistent with the findings of Xu et al ( 39 ). This suggests that the synergistic effect of dexmedetomidine and anesthetics can significantly reduce the dosage of propofol and opioids, thereby reducing the incidence of nausea and vomiting.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found intranasal dexmedetomidine resulted in a dose-dependent increase in both LMA-removal time and length of stay in the PACU, but it did not prolong the time to hospital discharge. In contrast with the results of our study, Li et al 25 and Xu et al 21 reported premedication with 2 μg kg −1 intranasal dexmedetomidine did not prolong postoperative recovery time or LMA removal time after total intravenous anaesthesia. Yao et al 14 noted that 1 or 2 μg kg −1 intranasal dexmedetomidine resulted in only a little longer emergence times but did not prolong the length of stay in the PACU for children undergoing unilateral strabismus surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results suggest that a younger age significantly increases the risk of emergence agitation, but dexmedetomidine had a similar effect in reducing the incidence of emergence agitation in children of all ages. According to the dose–response relation, the calculated ED 95 was 1.99 μg kg −1 , similar to the clinically recommended dose for children aged 1 to 18 years in a systematic review 21 . In our study, the ED 95 value for intranasal dexmedetomidine in preventing emergence agitation in younger children is higher.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Sevoflurane has the characteristics of rapid induction, rapid recovery, and stable efficacy, which has been widely used in clinical anesthesia [ 1 ]. Due to surgical trauma, general anesthesia, endotracheal intubation stimulation, and environmental factors, patients under sevoflurane anesthesia have a high probability of complications such as emergence agitation [ 2 , 3 ]. To reduce the incidence of complications such as the emergence agitation, chills, and hypotension in patients with general anesthesia, it is necessary to use a certain dose of sedative and analgesic drugs to relieve clinical symptoms [ 4 ].…”
Section: Introductionmentioning
confidence: 99%